투기거래자의 투자성과, 선물가격 예측능력 및 이익지속성 분석 - 서충원, 신연수 (무역연구, 2017)
In the futures market, the main issues are the speculators who takes risk from hedger earn the profit from futures trades, the reason that speculators make the profit, and their earning persistence over trades. But the researches on this subject are a few, because data are scarce. In this study, by using the unique data which identify each speculator’s profit and loss over intraday, day, and months. we analyze the speculator’s performance and their forecasting ability on the futures price, and persistence on trades. we use data form the Korea Treasury Bond Futures (KTB). By using the transaction audit and spot market features, we classify the individual trader as speculator. We divide individual investor into three groups as small, medium and large individual investor based on the total ontract over the research period. Main results are as follows. First, among 230 large traders, 186 traders gain the profit, 45 traders have losses. Second using Hartzmark (1991) methodologies about forecasting ability, large traders have nearly no forecasting capability of the futures price. Third, examining speculator’s earning persistence based Brown and Goetzmann (1995) and Goetzmann and Ibbotson (1994). speculators have the ability to get the profit continuously from the transaction, This, speculator’s profit source are not forecasting capability of the present price and luck. In this study, We conclude that speculators make profit by the market dominance, investment strategy of the investor, and etc. Consequently, it is necessary to regulate speculator trading in KTB. KCI Citation Count: 0